AN ANALYSIS OF DEPTH DOSE CHARACTERISTICS OF PHOTON IN WATER - Buzdar, Saeed Ahmad; Rao, Muhammad Afzal; Nazir, Aalia (Journal of Ayub Medical College Abbottabad, 2009)
Background: Photon beam is most widely being used for radiation therapy. Biological effect of radiation is concerned with the evaluation of energy absorbed in the tissues. It was aimed to analyse the depth dose characteristics of x-ray beams of diverse energies to enhance the quality of radiotherapy treatment planning. Methods: Depth dose characteristics of different energy photon beams in water have been analysed. Photon beam is attenuated by the medium and the transmitted beam with less intensity causes lesser absorbed dose as depth increases. Relative attenuation on certain points on the beam axis and certain percentage of doses on different depths for available energies has been investigated. Results: Photon beam depth dose characteristics do not show identical attributes as interaction of x-ray with matter is mainly governed by beam quality. Attenuation and penetration parameters of photon show variation with dosimetric parameters like field size due to scattering and Source to Surface Distance due to inverse square law, but the major parameter in photon interactions is its energy. Conclusion: Detailed analysis of photon Depth Dose characteristics helps to select appropriate beam for radiotherapy treatment when variety of beam energies available. Evaluation of this type of characteristics will help to establish theoretical relationships between dosimetric parameters to confirm measured values of dosimetric quantities, and hence to increase accuracy in radiotherapy treatment. Keywords: Radiotherapy, Treatment Planning, Photon beam, Absorbed Dose